Intense competition period impacts on heart rate variability in 8 elite swimmers - Hellard, P.; Caudal, N.; Nanoorenberg, P.; Schmitt, L.; Lacoste, L.; Cervetti, J. P.; Rey, J. L.; Fauquet, C. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Heart rate variability (HRV) analysis is a well recognized method to assess autonomic nervous system perturbations. HRV was shown to be influenced by fitness and fatigue in endurance athletes (Pichot et al., 2000). Increase in sympathetic tone was chronically experienced by athletes who were overtrained due to an intense anaerobic training regimen. In contrast, parasympathetic tone predominated in athletes who increased the training volume to a great extent (Hedelin et al., 2000). Intense anaerobic loads and severe psycho-emotional stress characterize competitions periods. Therefore, the aim of this study was to compare heart rate variability before and after the 8 days French national championships. Method RR intervals were recorded during 10 min in supine position and 5 min with imposed breathing (15/min). This test was performed just before and after the France championships at 9 am, by using a Polar® S810 heart rate monitor. Fast Fourier transform (FFT) and wavelet transform (WT) methods were used for the spectral analysis. Mean HR, standard deviation of all RR intervals (SDNN) and the percentage of successive interval differences larger than 50 ms (PNN 50) were used as time-domain measures of HRV. Peaks were then extracted from the spectrum and determined on very low frequency (VLF, between 0.00 Hz and 0.04 Hz), low frequency (LF, between 0.04 Hz and 0.15 Hz) and high frequency (HF, between 0.15 Hz and 0.5 Hz). This allowed us to determine total power (TP), VLF, LF and HF and compute the LF/HF ratio. Results TP, VLF and LF were lower after the championships (6318, 1684 and 1089 ms².hertz-1) than before (14508, 2924, and 5388 ms².hertz-1) with FFT, in imposed breathing (p=0.09, p < 0.05 and p<0.05, respectively). The same trend was obtained with WT (not significant). No concluding results were obtained in supine position. Discussion and conclusion TP, VLF and LF decreased during intense competitions periods. These results do not confirm that intensive training shifted the cardiac autonomic balance of the sympathetic over the parasympathetic drive (Pichot et al, 2000). Therefore, these results suggest a sympathetic system inhibition as the consequence of severe anaerobic loads and total psycho-emotional stress (Kuipers et Kaiser, 1998).